2008
DOI: 10.1002/gea.20237
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene and Early Holocene lake‐level fluctuations in the Lahontan Basin, Nevada: Implications for the distribution of archaeological sites

Abstract: The Great Basin of the western U.S. contains a rich record of late Pleistocene and Holocene lake-level fluctuations as well as an extensive record of human occupation during the same time frame. We compare spatial-temporal relationships between these records in the Lahontan basin to consider whether lake-level fluctuations across the Pleistocene-Holocene transition controlled distribution of archaeological sites. We use the reasonably well-dated archaeological record from caves and rockshelters as well as resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 53 publications
3
60
0
Order By: Relevance
“…At the Last Glacial Maximum, climate models simulate a splitting of the jet stream and a southward displacement of the westerly storm track due to the presence of the ice sheet (COHMAP Members, 1988;Bromwich et al, 2004;Kim et al, 2008). Recent proxy comparisons with the Paleoclimate Model Intercomparison Project ensembles suggests that (Vacco et al, 2005); MC (purple) and ML (red) d 18 O; MC (green) and ML (blue) d 13 C; Lake level as % maximum for Lake Franklin (green line; Munroe and Laabs (2013), Lake Lahontan (black line; Benson et al, 1995;Adams et al, 2008), and Lake Bonneville (gray line; Oviatt et al, 1992;McGee et al, 2012) (after Ibarra et al, 2014; Lake Elsinore leafwax d 2 H (Kirby et al, 2013); Leviathan speleothem d 18 O (Lachniet et al, 2014); Cave of the Bells speleothem d 18 O (Wagner et al, 2010); Fort Stanton speleothem d 18 O (Asmerom et al, 2010); and U isotope ratios (Polyak et al, 2012). Dashed lines separate time intervals described in the text with gray shading designating the cold/wet intervals noted in the ML1 record.…”
Section: Mechanisms For Precipitation Change In Western North Americamentioning
confidence: 94%
See 1 more Smart Citation
“…At the Last Glacial Maximum, climate models simulate a splitting of the jet stream and a southward displacement of the westerly storm track due to the presence of the ice sheet (COHMAP Members, 1988;Bromwich et al, 2004;Kim et al, 2008). Recent proxy comparisons with the Paleoclimate Model Intercomparison Project ensembles suggests that (Vacco et al, 2005); MC (purple) and ML (red) d 18 O; MC (green) and ML (blue) d 13 C; Lake level as % maximum for Lake Franklin (green line; Munroe and Laabs (2013), Lake Lahontan (black line; Benson et al, 1995;Adams et al, 2008), and Lake Bonneville (gray line; Oviatt et al, 1992;McGee et al, 2012) (after Ibarra et al, 2014; Lake Elsinore leafwax d 2 H (Kirby et al, 2013); Leviathan speleothem d 18 O (Lachniet et al, 2014); Cave of the Bells speleothem d 18 O (Wagner et al, 2010); Fort Stanton speleothem d 18 O (Asmerom et al, 2010); and U isotope ratios (Polyak et al, 2012). Dashed lines separate time intervals described in the text with gray shading designating the cold/wet intervals noted in the ML1 record.…”
Section: Mechanisms For Precipitation Change In Western North Americamentioning
confidence: 94%
“…We note here that BL is ventilated during the cold winter months, during which drip rates also increase substantially. Monthly measurements of rain and drip water d 18 O at Black Chasm Cavern documented that rainwater d 18 O is significantly positively correlated with surface air temperature, but shows no significant relationship (Vacco et al, 2005); LS ¼ Lake Surprise (Ibarra et al, 2014): LL: Lake Lahontan (Benson et al, 1995;Adams et al, 2008); LF ¼ Lake Franklin (Munroe and Laabs, 2013); LB ¼ Lake Bonneville (McGee et al, 2012); MC ¼ Moaning Cave; ML ¼ McLean's Cave; SL ¼ Swamp Lake (Street et al, 2012); LV ¼ Leviathan (Lachniet et al, 2014); LEL ¼ Lake Elsinore (Kirby et al, 2013); COB ¼ Cave of the Bells (Wagner et al, 2010); LE ¼ Lake Estancia (Broecker and Putnam, 2012); FS ¼ Fort Stanton Cave (Asmerom et al, 2010). B) Location of McLean's Cave (ML; 38 4.20 0 N, 120 25.20W; elevation of 300 m above sea level) in the western foothills of the Sierra Nevada with location of Black Chasm Cavern (BL; Oster et al, 2012) and Moaning Cave (MC; Oster et al, 2009 (Oster et al, 2012).…”
Section: Site and Sample Descriptionmentioning
confidence: 97%
“…Broecker, 2010;Hostetler and Benson, 1990;Munroe and Laabs, 2013). Geomorphological and geochronological studies on the sediments both from ancient highstands and lake beds showed that during the Heinrich Stadial 1, massive lakes dominated in the vast hydrologically closed and semi-closed basins, stretching from Lake Lahontan (Adams et al, 2008;Benson et al, 1990) and Lake Bonneville (McGee et al, 2012;Oviatt et al, 1992) as far north as ∼42 • N, to Lake Russell at ∼38 • N , and even further south to Lake Estancia at ∼35 • N (Allen and Anderson, 2000). These lakes ubiquitously endured a dramatic lake level drop or even completely dry-out during the Bølling-Allerød period when the North Atlantic was warm.…”
Section: Itcz Shift and The Subtropical Jetsmentioning
confidence: 99%
“…The connected sub-basins during Lake Lahontan's high stands may have provided dispersal corridors for aquatic taxa (Reheis, 1999), and appear to have done so for some minnows (Chen, Parmenter & May, 2007;Chen, Reid & May, 2009). With the onset of the Holocene, water levels dropped, again leaving most of Lake Lahontan's sub-basins isolated from one another (Negrini, 2002;Adams et al, 2008).…”
Section: Introductionmentioning
confidence: 95%